TEACHER TRAINING AND DEVELOPMENT IN ELT: A PROFESSIONAL APPROACH - Frank Farmer (Indonesian JELT, 2006)
English Language Teaching (ELT) has no professional body controlling entry to the profession, and there is a lack of clarity in the literature on the role and content of both pre-service teacher education and in-service teacher development. This paper builds on socioeconomic models of professionalism in an attempt to develop valid criteria for both. Professionalism as a system of rewarding and controlling expert labour is defined and the legitimacy of forming professional bodies is discussed. The criteria are then applied to ELT as a critique of existing pre-service and in-service teacher education, and suggestions are made for the professionalization of ELT. Keywords: professionalism, pre-service education, in-service education, ELT.